2019
DOI: 10.1111/echo.14284
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of edge‐to‐edge percutaneous mitral valve repair on the shape and size of the mitral annulus and its relation to mitral regurgitation

Abstract: Background The effects of edge‐to‐edge percutaneous mitral valve repair on the shape and size of the mitral annulus and its relation to mitral regurgitation (MR) have not been well characterized. We evaluated acute changes in mitral annular shape and dimensions, and their effect on MR severity, in patients with functional and degenerative MR following MitraClip®. Methods Patients that underwent MitraClip® between January 2013 and May 2016 at our institution were retrospectively reviewed. Exclusions: inadequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
(37 reference statements)
2
21
0
Order By: Relevance
“…Thus far, several 3D TEE studies have suggested geometrical effect with regard to MV annulus diameter during MitraClip implantation in patients with FMR. These studies discovered reduction in AP diameter in FMR 4,5,18 and demonstrated its association with MR improvement 3,4 …”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Thus far, several 3D TEE studies have suggested geometrical effect with regard to MV annulus diameter during MitraClip implantation in patients with FMR. These studies discovered reduction in AP diameter in FMR 4,5,18 and demonstrated its association with MR improvement 3,4 …”
Section: Discussionmentioning
confidence: 90%
“…The AP diameter reduction by MitraClip in degenerative MR remained controversial 3,5,18,19 . A more recent study by Patzelt et al indicated reduction in MV annulus AP diameters in a larger cohort of 77 patients with DMR and showed its correlation with residual MR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to annuloplasty devices, future studies are required to identify which patients and specifically anatomies are most suited to treatment with leaflet plasty devices. In particular, leaflet devices could be useful in patients with combined annular dilatation and leaflet remodeling (leaflet tethering) because of their capacity to reshape the TV and indirectly reduce annular dimensions ( 14 , 23 ). However, the following points need to be addressed in the future: ◾ Residual regurgitation and how to achieve good procedural results .…”
Section: Which Device For Which Patient? Moving Toward a Tailored Appmentioning
confidence: 99%